Inorganic polyphosphate in Dictyostelium discoideum: Influence on development, sporulation, and predation - Zhang, Haiyu (National Academy of Sciences, 2005)
Dictyostelium discoideum, a social slime mold that forms fruiting bodies with spores, depends on inorganic polyphosphate (poly P) for its cycles of development and for nutritional predation on bacteria. The synthesis of poly P, a polymer of tens or hundreds of phosphate residues linked by high energy, ATP-like bonds, is catalyzed in most bacteria by poly P kinase (PPK1). The eukaryote D. discoideum possesses a homolog of PPK1. We report here that mutants of D. discoideum PPK1 (DdPPK1) have reduced levels of poly P and are deficient in development. Fruiting bodies are smaller and produce fewer spores, which appear to germinate like the wild type (WT). The DdPPK1 mutant formed smaller plaques on bacterial lawns compared with those of the WT. Predation by D. discoideum, assessed by uptake and digestion of Klebsiella aerogenes, showed that fewer bacteria were taken up by the DdPPK1 mutant compared with the WT and were killed less rapidly, indicating a role of poly P and/or DdPPK1 in phagocytosis. On Pseudomonas aeruginosa lawns, cleared plaques were observed with the bacterial PPK1 mutant but not with the WT P. aeruginosa. Thus, poly P is important in predation both for the predator and prey.